Metacognitive strategies and writing proficiency: mediating role of critical thinking skills in online learning mode during COVID-19 - Shen, Xiaolei; Ismail, Lilliati; Jeyaraj, Joanna Joseph (Universiti Putra Malaysia, 2024)
The development of cognitive abilities among EFL learners remains underexplored within English as a foreign language, especially in online writing activities during the COVID-19 era. Enhancing writing proficiency in EFL learners necessitates a heightened cognitive awareness, encompassing the utilization of critical thinking skills and metacognitive strategies. However, existing studies primarily focused on the direct relationship between metacognitive strategies and writing proficiency or critical thinking skills and writing proficiency, overlooking the mediating role of critical thinking skills in online environments. This study sought to bridge this research gap by investigating the interplay among metacognitive strategies, critical thinking skills, and writing proficiency. Specifically, it explores how critical thinking skills mediate the relationship between metacognitive strategies and writing proficiency online. The study involved 459 EFL participants who completed the California Critical Thinking Skills Test, a metacognitive strategies questionnaire, and an IELTS writing test. Data analysis included descriptive, Pearson correlation, and bootstrap analysis for comprehensive examination. The findings unveiled significant correlations among metacognitive strategies, critical thinking skills, and EFL learners’ writing proficiency. Of particular note was the mediation of critical thinking skills between metacognitive strategies and writing proficiency, highlighting the pivotal role of critical thinking skills in online writing contexts. These outcomes emphasized the significance of metacognitive strategies in online writing environments. Future research endeavors could illuminate these dynamics through longitudinal studies across different learning stages.